Papillary Renal Cell Carcinoma in Lynch/Muir-Torre Syndrome with Germline Pathogenic Variant in MSH6 and Molecular Analysis: Report of a Case and Review of the Literature (Journal of Kidney Cancer, 2021)
Lynch syndrome (LS) is an autosomal dominant inherited disorder due to pathogenic variations in the mismatch repair genes, which predisposes to malignancies, most commonly colon and endometrial carcinoma. Muir-Torre syndrome is a subset of LS with cutaneous sebaceous adenoma and keratoacanthoma in addition to the malignancies. Renal cell carcinoma (RCC) in patients with LS is extremely rare. Only 26 cases have been reported and among them, only two cases of papillary RCC. We report a case of synchronous papillary RCC and colonic adenocarcinoma in an 85-year-old male with Lynch/Muir-Torre syndrome. The LS was diagnosed when he presented with multiple sebaceous adenomas and genetic testing showed a pathogenic variant in MSH6 mismatch repair gene. A colonoscopy at that time showed multiple tubular adenomas with high-grade dysplasia. He was lost to follow-up and presented with gastrointestinal bleeding after 20 years. A right colonic mass, and a solid mass in the lower pole of the right kidney, was detected by imaging. Right Colectomy showed a T3N0 mucin-producing adenocarcinoma. Right nephrectomy showed a T3a papillary RCC which was microsatellite stable with MSH6, and KRAS mutation. The 36-month follow-up exams showed additional sebaceous neoplasms, and an absence of metastatic carcinoma. Analysis of the reported cases of RCC in LS show clear cell RCC as the most common type. These tumors showed MLH1 mutation most commonly, unlike the urothelial malignancies in LS which involve MSH2. Among the 4 cases of RCC with MSH6 mutation, three were in females, indicating some gender differences.